Lobster Ecolabelling - Ward, T.; Phillips, Bruce (John Wiley & Sons, Ltd, 2013)
Both small- and industrial-scale lobster fisheries were among the first wild-catch fisheries to have been certified and ecolabelled. This chapter reviews the basic principles of ecolabelling as it applies to lobster fisheries and aquaculture, and describes the global trends in the certification of farmed and wild-catch spiny and clawed lobsters. We describe the four extant lobster fisheries certified by the Marine Stewardship Council (MSC), and discuss issues raised by the MSC assessment process. We discuss the motivations of the different actors with an interest in lobster ecolabelling, and provide an example set of criteria to guide a benchmarking assessment (relative comparison) of the performance of a selected set of aquaculture ecolabelling systems. Our analysis revealed that among the systems we considered there are at least five major weaknesses that need corrective attention to provide for more robust assessment and ecolabelling systems for lobsters – a lack of consistency, limited transparency, lack of explicit standards, imprecise technical specifications and limited capacity for verification. We found that that the costs and benefits from ecolabelling are strongly differentiated across the scales, and particularly with respect to the environmental and social benefits derived from the certification assessment process and outcomes. The lack of global consistency and accuracy across certification schemes, and the dynamics of the certification marketplace, have important but different consequences across the scales, leading to different and often unrealistic expectations from both fishers/producers and consumers. Without correction, this will lead to eventual decay in the value of ecolabelling systems for all seafoods.